Emergence of visceral leishmaniasis in Kollam district, Kerala, southern India - Sandhya, R.; Rakesh, P. S.; Dev, Soumya (International Journal Of Community Medicine And Public Health, 2019)
An outbreak investigation was initiated following an unusual occurence of kala azar reported among people residing in the tribal belt of Kulathupuzha area, eastern part of Kollam district, Kerala, Southern India. 2 cases of kala azar were investigated during 2016-2018. Epidemiological analysis indicated no epidemiological link between the cases. However the Visceral leishmaniasis and cutaneous leishmaniasis intruding into newer regions pose a major threat to ongoing leishmaniasis elimination and maintenance programs.